1994
DOI: 10.1159/000262008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a 3-Year Professional Flossing Program with Chlorhexidine Gel on Approximal Caries and Cost of Treatment in Preschool Children

Abstract: The aim was to evaluate the effect of chlorhexidine gel treatment on the incidence of approximal caries in preschool children. One hundred and seventeen 4-year-olds, divided into two groups, participated: (1) chlorhexidine gel group (n = 59), and (2) placebo gel group (n = 58). Group 1 was treated 4 times a year with a 1% chlorhexdine gel and group 2 with a placebo gel. Approximately 0.7 ml of gel was applied interdentally by means of a flat dental floss. A control group (group 3), which did not receive any fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 10 publications
0
26
0
Order By: Relevance
“…In addition, a study by Gisselsson et al . showed that after 3 years, the number of caries lesions was lower in children that used dental floss combined with chlorhexidine 1% gel than in children that used dental floss and a placebo gel.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, a study by Gisselsson et al . showed that after 3 years, the number of caries lesions was lower in children that used dental floss combined with chlorhexidine 1% gel than in children that used dental floss and a placebo gel.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, in Scandinavian populations, between 30 and over 50% of these surfaces show radiographic evidence of caries not detected from clinical examination alone [Boman et al, 1999;Raadal et al, 2000]. Progression of approximal lesions in primary molars can be prevented or retarded [Gisselsson et al, 1994], so, early detection of approximal enamel lesions is important. …”
mentioning
confidence: 99%
“…Details of the 3-year fl ossing program and its effect on the development of approximal caries have been reported elsewhere [Gisselsson et al, 1988[Gisselsson et al, , 1994. Briefl y, during the experimental years (the preschool children 1987-1990 and the teenagers 1980-1983), the caries preventive treatment included regular professional fl ossing with a 1% CHX gel (Hibitane Dental, ICI, Macclesfi eld, UK) or a placebo gel, carried out 4 times per year.…”
Section: The Professional Flossing Programmentioning
confidence: 99%
“…The method is both simple and cheap compared to the tray method and can therefore be applied to a large group of individuals considered to be at risk for developing dental caries. The method has been evaluated both and in 4-to 7-year-old preschool children [Gisselsson et al, 1994] and in 12-to 15-year-old teenagers [Gisselsson et al, 1988]. After 3 years, the approximal caries reduction was around 40% compared to a placebo gel or a no gel treatment.…”
mentioning
confidence: 99%